Predictors of 12-month outcome in bulimia nervosa and the influence of attitudes to shape and weight. - Fairburn, C; Peveler, R; Jones, R; Hope, R; Doll, H (1993)
Seventy-five patients with bulimia nervosa were treated with 1 of 3 short-term psychological treatments and were then entered into a closed 1-year period of follow-up. Pretreatment predictors of 3 measures of outcome were sought. Only 2 variables were significantly associated with outcome: attitudes toward shape and weight, and self-esteem. The nature of the relation between attitudinal disturbance and outcome was complex and unexpected. The data set was also used to test the major prediction of the cognitive view of bulimia nervosa, namely that among patients who have responded to treatment, the residual level of attitudinal disturbance will predict subsequent outcome. This prediction was confirmed.